Toxicity of cyanobacterial blooms from the reservoir Valle de Bravo (Mexico): A case study on the rotifer Brachionus calyciflorus - Nandini, S.; Sánchez-Zamora, C.; Sarma, S.S.S. (The Science of the total environment, 2019)
Proliferating cyanobacterial blooms due eutrophication in reservoirs is a major global problem. The production of cyanotoxins often increases with grazing pressure and temperature while the sensitivity of zooplankton to cyanotoxins is directly related to temperature. Here we evaluate the effect of different concentrations of the crude extract of cyanobacteria from Valle de Bravo reservoir during dry (January) and rainy (September) seasons at 20 and 25 °C on the rotifer Brachionus calyciflorus based on acute and chronic toxicity tests. We filtered 20 or 150 l of lake water, depending on the intensity of the bloom, and estimated the density and diversity of the cyanobacteria. The crude extracts, after 5 cycles of freezing, thawing and sonication at 14 MHz, were filtered and the microcystin concentration quantified based on ELISA. The extracts were used to conduct the acute and chronic toxicity tests, all in quadruplicate. Acute toxicity tests were based on 24 h mortality. Chronic toxicity tests (population growth and life table experiments) were conducted at 5 and 10% of the median lethal concentration. The field samples were dominated by Microcystis sp. (January) or Woronichinia naegeliana (September). The microcystin concentration in lake water was 9.57 μg/l and 0.097 μg/l and the median lethal concentration was 5.34 μg microcystin/L and 0.35 μg microcystin/L in January and September, respectively. Survival and reproduction of B. calyciflorus were lower in the presence of the cyanobacteria crude extract, more so at 20° than at 25 °C. Our results highlight the urgency of regular monitoring based on zooplankton assays for reservoirs in tropical and temperate regions, subject to frequent and dominant cyanobacterial blooms, often as a result of climate change. [Display omitted] •Valle de Bravo reservoir, source of drinking water, suffers frequent cyanobacterial blooms.•Cyanobacteria extract from Valle de Bravo reservoir was tested for toxicity.•Brachionus calyciflorus was more sensitive at 25° than at 20 °C.•Samples with Microcystis were less toxic than those with Woronichinia.